Effects of caregiver dementia training in caregiver‐patient dyads: A randomized controlled study. (22nd July 2020) - Birkenhäger‐Gillesse, Elizabeth G.; Achterberg, Wilco P.; Janus, Sarah I.M.; Kollen, Boudewijn J.; Zuidema, Sytse U.
Abstract : Objectives: Caregivers for people with dementia (PWD) have reported needing emotional and social support, improved coping strategies, and better information about the illness and available support services. In this study, we aimed to determine the effectiveness of an Australian multicomponent community‐based training program that we adapted and implemented in a non‐medical Dutch health care setting. Methods and design: A randomized controlled trial was performed: 142 dyads of cohabiting caregivers and PwD were randomized to control (care as usual) or intervention (training program) groups and outcomes were compared. Programs lasted 1 week, comprised 14 sessions, and were delivered by specialist staff. We included 16 groups of two to six caregivers. The primary outcome was care‐related quality of life (CarerQol‐7D) at 3 months. The main secondary outcomes for caregivers were self‐rated burden, health and mood symptoms, and for PwD were neuropsychiatric symptoms, quality of life, and agitation. Results: No significant difference was observed for the primary outcome. However, caregivers experienced fewer role limitations due to physical function (adjusted mean difference, 13.04; 95% confidence interval [95%CI], 3.15‐22.93), emotional function (13.52; 95%CI, 3.76‐23.28), and pain reduction (9.43; 95%CI, 1.00‐17.86). Positive outcomes identified by qualitative analysis included better acceptance and coping and improved knowledge of dementia and available community services and facilities. Conclusion: Quantitative analysis showed that the multicomponent course did not affect care‐related quality of life but did have a positive effect on experienced role limitations and pain. Qualitative analysis showed that the course met the needs of participating dyads.